Porphyromonas Gingivalis fim A Type I, II, III, IV, V and Ib Genotypes Distribution among Malay Chronic Periodontitis Patients - Tara Bai Taiyeb Ali (Journal of Global Pharma Technology, 2020)
III, IV, V and Ib genotypes in the Malay ethnic group and to relate their presence to chronic periodontitis. Design: A total of 30 Malay subjects (15 periodontitis and 15 periodontally healthy subjects) aged 25 years and above were selected. Clinical periodontal parameters were recorded for each subject. Subgingival plaque samples were collected from the deep pockets ≥5mm in periodontitis subjects and from subgingival areas in healthy subjects. Presence of P. gingivalis fimA types I, II, III, IV, V and Ib genotypes were identified by polymerase chain reaction followed by agarose gel electrophoresis.  Results: P. gingivalis was more prevalent in periodontitis subjects (53.33%) as compared to periodontally healthy subjects (13.33%). In periodontitis subjects, P. gingivalis fimA I, II, IV, V and Ib genotypes were detected in of 20%, 33.33% 20%, 6.67% and 13.33% respectively among periodontitis subjects. The frequency of genotype fimA type II was greater where plaque accumulation was >1. However, P. gingivalis fimA IV genotype followed by fimA Ib genotype were detected in higher percentages. Conclusion: P. gingivalis was detected in periodontally diseased and healthy subjects. P. gingivalis fimA genotype II, IV and Ib was identified in diseased subjects only. In conclusion, the prevalence of P. gingivalis especially fimA genotype II, IV and Ib can be used as indicator to differentiate between diseased and healthy subjects.Keywords: P. gingivalis, Chronic periodontitis, Genotypes.